Pengaruh Kredibilitas Konten TikTok @dokterdetektif terhadap Minat Beli Produk Skincare - Asriv Nurul Al Faris; Qoryna Noer Seyma; Asep Soegiarto; Mentari Anugrah Imsa; Abdul Kholik (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The skincare industry has experienced rapid growth accompanied by excessive promotional claims lacking scientific basis, prompting the need for credible educational content. The TikTok account @dokterdetektif emerged in response to this issue by presenting products reviews based on laboratory test results. This study aims to measure the extent to which the credibility of @dokterdetektif TikTok account influences purchase intention of skincare products. A quantitative research method with a survey approach was used, involving 100 respondents who follow the @dokterdetektif account. The research instrument was developed based on Source Credibility Theory (expertise, trustworthiness, attractiveness) and purchase intention indicators (transactional, preferential, referential, exploratory). The results of a simple linear regression test show that the t value 10.456 > t table 1,984 with a significance level < 0.05, and a coefficient of determination (R2) of 0.527, indicating that content credibility explains 52,7% of the variation in purchase intention. These findings conclude that credible educational content on TikTok significantly influences purchase intention and has the potential to be an effective digital communication strategy on social media.